Retrospective analysis of nystagmus characteristics and clinical applications of positional testing in patients with cupulolithiasis of the posterior semicircular canal in benign paroxysmal positional vertigo - Wu, Jing; Zou, Yihuai; Xu, Wenyan; Ma, Hongming; Huang, Lixian; Zhao, Bo; Sun, Liman (Frontiers in Neurology, 2024)
Objective: To investigate the characteristics of positional nystagmus in patients with cupulolithiasis of the posterior semicircular canal benign paroxysmal positional vertigo (PC-BPPV-cu) to improve clinical diagnostic accuracy.This study retrospectively analyzed 128 cases of PC-BPPV-cu and 128 of canalolithiasis of BPPV (PC-BPPV-ca). General data, intensity, distribution, and correlation of positional nystagmus were compared between the two groups.Results: Compared to the PC-BPPV-ca group, more cases in the PC-BPPV-cu group initially presented in the emergency department (P <0.05). The most frequent positional nystagmus induced by PC-BPPV-cu was torsional-up beating nystagmus, characterized by the upper pole of the affected eye beating towards the lower ear and vertically upward (387 cases, 59.7%). It was followed by torsional-down beating nystagmus, characterized by the upper pole of the unaffected eye beating towards the lower ear and vertically downward (164 cases, 25.3%). The former represented posterior canal excitatory nystagmus (PC-EN), while the latter represented posterior canal inhibitory nystagmus (PC-IN). In the PC-BPPV-cu group, PC-EN was most easily caused by the half Dix-Hallpike maneuver (HH) on the affected side, and PC-IN was most easily induced by a face-down position (FDP) on the unaffected side at approximately a 45°(45°FDP). The vertical slow phase velocity (v-SPV) of positional nystagmus in the affected HH was more potent than in other positions with PC-EN (all P <0.05); the v-SPV of positional nystagmus in 45°FDP was greater than that in different positions with PC-IN (all P <0.05); the v-SPV of the affected Dix-Hallpike (DH) in the PC-BPPV-ca group was significantly greater than that of the affected HH in the PC-BPPV-cu group (P <0.05). Apriori analysis showed the strongest correlation with HH positional nystagmus was the affected side roll-test, followed by DH.In the PC-BPPV-cu group, HH most easily induced PC-EN on the affected side, and PC-IN was most easily induced by 45°FDP. Some PC-BPPV-cu cases did not observe significant nystagmus induced in the DH position on the affected side; however, vertical rotation nystagmus was induced in the roll-test position on the affected side. In such cases, PC-BPPV-cu diagnosis should be considered, and the HH and 45°FDP tests should be conducted to support the diagnosis.